2023
DOI: 10.7759/cureus.46615
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Orthodontic Brackets and Their Application in Clinical Orthodontics

Vedanti V Mundhada,
Vikrant V Jadhav,
Amit Reche

Abstract: Braces are undoubtedly a blessing for those whose teeth are misaligned in various ways, yet many people may not enjoy the traditional metal braces. However, some people are totally fine with having their teeth fused with the set of metal brackets and various metal components flowing through. A few people may simply not feel comfortable in that way. Orthodontists have developed a huge array of bracket styles by concentrating on the wide range of preferences and financial constraints that their patients present.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 37 publications
(53 reference statements)
1
0
0
Order By: Relevance
“…Nkenke et al [ 18 ] noted that bond strength should not surpass 10 MPa, which is the tensile strength of enamel. The mean SBS values obtained in this study exceed 6–8 MPa, reported in the literature as a clinically acceptable standard for in vitro SBS testing [ 1 , 6 , 19 , 20 ]. Because higher bond strength values can be associated with possible iatrogenic damage to the enamel surface, one should be cautious when debonding any brackets which exceed these values [ 8 ].…”
Section: Discussionsupporting
confidence: 61%
“…Nkenke et al [ 18 ] noted that bond strength should not surpass 10 MPa, which is the tensile strength of enamel. The mean SBS values obtained in this study exceed 6–8 MPa, reported in the literature as a clinically acceptable standard for in vitro SBS testing [ 1 , 6 , 19 , 20 ]. Because higher bond strength values can be associated with possible iatrogenic damage to the enamel surface, one should be cautious when debonding any brackets which exceed these values [ 8 ].…”
Section: Discussionsupporting
confidence: 61%
“…The most frequently used preadjusted orthodontic appliance for the last 3 decades is the fixed appliances with stainless steel brackets and the ceramic brackets come secondly (24,25) . In a study conducted by Keim et al (2014) demonstrated that some kind of self-ligating system was used by most of the orthodontists (63%), while just 20% of them used esthetic brackets (26) .…”
Section: Figurementioning
confidence: 99%